2009
DOI: 10.1523/jneurosci.3753-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Scaling Requires the GluR2 Subunit of the AMPA Receptor

Abstract: Two functionally distinct forms of synaptic plasticity, Hebbian long-term potentiation (LTP) and homeostatic synaptic scaling, are thought to cooperate to promote information storage and circuit refinement. Both arise through changes in the synaptic accumulation of AMPA receptors (AMPARs), but whether they use similar or distinct receptor-trafficking pathways is unknown. Here, we show that TTX-induced synaptic scaling in cultured visual cortical neurons leads to the insertion of GluR2-containing AMPARs at syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
237
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(258 citation statements)
references
References 51 publications
(97 reference statements)
20
237
1
Order By: Relevance
“…GRIP1 was necessary for synaptic scaling, because scaling up was prevented by shRNA-mediated knock down (KD) of endogenous GRIP1 and rescued by replacement with an RNAi-insensitive (RNAiI) GRIP1 but not a GRIP1 mutant that lacks the GluA2 interaction domain. We showed previously that GluA2 KD blocks synaptic scaling (12). Here, we show that synaptic scaling after GluA2 KD can be rescued by wild-type (RNAiI) GluA2 or point mutants that do not interfere with GRIP1 binding but not by GluA2 point mutants (Y876E and S880E) that reduce GluA2-GRIP1 binding, strongly suggesting that GRIP1 mediates synaptic scaling through interactions with GluA2.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…GRIP1 was necessary for synaptic scaling, because scaling up was prevented by shRNA-mediated knock down (KD) of endogenous GRIP1 and rescued by replacement with an RNAi-insensitive (RNAiI) GRIP1 but not a GRIP1 mutant that lacks the GluA2 interaction domain. We showed previously that GluA2 KD blocks synaptic scaling (12). Here, we show that synaptic scaling after GluA2 KD can be rescued by wild-type (RNAiI) GluA2 or point mutants that do not interfere with GRIP1 binding but not by GluA2 point mutants (Y876E and S880E) that reduce GluA2-GRIP1 binding, strongly suggesting that GRIP1 mediates synaptic scaling through interactions with GluA2.…”
supporting
confidence: 51%
“…We showed previously that the GluA2 C-tail is required for TTX-induced synaptic scaling up (12). Here, we wished to determine the role of the GluA2 C-tail binding protein, GRIP1, in synaptic scaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that despite these reports, several studies have failed to detect the specific incorporation of CP-AMPARs during homeostatic scaling, e.g. 65 , suggesting this specific incorporation of CP-AMPARs may be dependent on the synapse, developmental stage and mode of induction. Thus, as for the proposed involvement of CP-AMPARs in LTP, the differential recruitment of CP-AMPAR during homeostatic scaling remains controversial.…”
Section: Cp-ampars In Synaptic Plasticitymentioning
confidence: 98%
“…AMPAR trafficking, binding, and modification are highly subunit-specific. It has been shown that the GluA2 subunit, but not GluA1, is required for inactivity-induced scaling, and the C-terminal domain is crucial (10). Many molecules known to regulate AMPAR trafficking, including AKAP5, Arc, TNFα, β3 integrins, PSD-95, and PICK1, are all involved in or required for synaptic scaling in neuronal cultures (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%